2015
DOI: 10.1080/19313152.2014.981775
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Hybridized Language Learning Spaces Through Translanguaging Pedagogy: Dual Language Preschool Teachers’ Languaging Practices in Support of Emergent Bilingual Children’s Performance of Academic Discourse

Abstract: In recent years, there has been a growing interest among policymakers, practitioners, and researchers in early bilingual development and the unique role of the educational setting's language policy in this development. In this article, we describe how one dual language preschool teacher, in partnership with two co-teachers, navigated the tensions between language separation ideology and its practical realization in early bilingual education by co-constructing and enacting flexible bilingual pedagogic practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(112 citation statements)
references
References 33 publications
6
105
0
1
Order By: Relevance
“…Idag ses flerspråkighet som en tillgång (ex. Garrity, Aquino-Sterling & Day, 2015;Gort & Sembiante, 2015;Strazer, 2018). Genom att barns flerspråkighet stimuleras kan språkutveckling och skolresultat förbättras vilket skiljer sig från en tidigare syn på flerspråkighet där språken sågs konkurrera med varandra (Walk mfl., 2015).…”
Section: Tidigare Forskningunclassified
“…Idag ses flerspråkighet som en tillgång (ex. Garrity, Aquino-Sterling & Day, 2015;Gort & Sembiante, 2015;Strazer, 2018). Genom att barns flerspråkighet stimuleras kan språkutveckling och skolresultat förbättras vilket skiljer sig från en tidigare syn på flerspråkighet där språken sågs konkurrera med varandra (Walk mfl., 2015).…”
Section: Tidigare Forskningunclassified
“…Buysse and colleagues (2010) found that even in situations where monolingual English-speaking teachers provide moderate quality instructional language and literacy practices, they use very few linguistically responsive practices to support DLLs. Gort and colleagues (2012, 2015) have examined the way in which preschool Spanish-English bilingual teachers use both languages with DLLs. For instance, during read-alouds, teachers ask differing types of questions when they read in Spanish versus English (Gort, Pontier, & Sembiante, 2012).…”
Section: High Quality Language and Literacy Practices For Dllsmentioning
confidence: 99%
“…Students' cultural and linguistic resources, or their "funds of knowledge" from home communities (Moll et al, 1992), are used to support academic learning as ELLs develop new resources to be able to participate in new situations, bridging home and school and enhancing opportunities for students to learn (Valenzuela, 1999). Teachers can draw on ELLs' bilingual repertoires as supports for culture (Martinez, Hikida, & Durán, 2015), as ELLs use their bilingual resources in classrooms as resources without artificial linguistic boundaries (Gort & Sembiante, 2015).…”
Section: Principles Of a Language-based Approach To Content Instructionmentioning
confidence: 99%